Study of Electric and Magnetic Properties of Iron-Modified MFI Zeolite Prepared by a Mechanochemical Method; Materials; Vol. 15, iss. 22 - Murrieta-Rico F. N. Fabian; Antúnez-García J. Joel; Yocupicio-Gaxiola R. I. Rosario; Zamora J. Jonathan; Reyes-Serrato A. Armando; Pestryakov A. N. Aleksey Nikolaevich; Petranovskii V. Vitalii (2022, 2022)
Title screen